Ferrofluid-assisted rapid and directional harvesting of marine microalgal Chlorella sp. used for biodiesel production. (November 2017) - Ho, Shih-Hsin; Chiu, Sheng-Yi; Kao, Chien-Ya; Chen, Tsai-Yu; Chang, Yu-Bin; Chang, Jo-Shu; Lin, Chih-Sheng
Graphical abstract: Highlights: High harvesting efficiency of 95–100% was achieved within 1 min with a ferrofluid dosage of 25 mg L −1 . A simple and effective strategy for microalgal harvesting by ferrofluid was demonstrated. The harvesting efficiency reached over 80% after five recycles by the ferrofluid-harvesting system. The growth reached 80% after three recycles by the ferrofluid-harvesting system. Abstract: In this work, a novel harvesting strategy using ferrofluids coupled with flocculation as a magnetic directional harvesting system was developed, providing a fast and easy way to effectively collect microalgae with no further modifications made to the ferrofluids. With a ferrofluid dosage of 25 mg L −1, a high harvesting efficiency of 95–100% was achieved within 1 min. In addition, we successfully performed a wastewater recycling strategy coupled with a microalgal ferrofluid-harvesting dynamic flow-through system to harvest biomass of Chlorella sp. MTF-7 which could achieve over 80% of the maximum level after three repeated recycling cultivations. This work demonstrated the use of an integrated microalgal ferrofluid-harvesting dynamic flow-through system to develop a simple and effective strategy to enhance microalgal harvesting efficiency, along with wastewater recycling, in a marine microalgal Chlorella sp. MTF-7.